Numerical study on the release and migration behavior of fission gas in a molten LBE pool - Mai, Zijun; Zhao, Zichen; Cheng, Hui; Cheng, Songbai; Zhao, Jiyun (Frontiers in Energy Research, 2022)
Lead-cooled Fast Reactor (LFR) is one of the most promising fast neutron reactors using molten lead or Lead-Bismuth Eutectic (LBE) alloy as coolant. Under postulated severe accidents, the fuel rod of LFR may be damaged, which would cause the release of fission gas, and the migration of fission gas bubbles in the reactor molten pool will affect the release and absorption of radioactive substances in the reactor. In this paper, three-dimensional numerical study on the release and migration behavior of fission gas in the molten LBE pool of LFR is carried out based on the VOF method. The bubbles are continuously released by gas injection, and the research mainly focuses on the detachment time, the rising velocity and the size of the bubble when it detaches at the orifice. The coalescence of bubbles is observed and the acceleration effect of the bubble wake is confirmed. The distribution of the bubble terminal rising velocity with diameter has no simple or linear relationship. The effects of the gas injection velocity, the release depth and the gas injection angle are studied. Lower gas injection velocity will delay the detachment and reduce the size of bubble. The increase of release depth tends to release smaller bubbles. The bubbles released from a vertical surface will attach to the wall. The simulations and theoretical analysis are comparable and have similar tendencies. The distribution of the bubble terminal rising velocity with equivalent diameter may predict the migration behavior of bubbles in molten LBE.